Experience of Healthcare Providers on Enteral Nutrition: Challenges and Ways to Improve Current Practice - Abd Kadir, Nor Syahiza; Zaman, Mazuin Kamarul; Ahmad Sharoni, Siti Khuzaimah; Mohd Fahmi Teng, Nur Islami (Jurnal Gizi dan Pangan, 2025)
The aim of this qualitative study is to explore the experience of Healthcare Providers (HCPs) in Enteral Nutrition (EN) practice in hospital settings, the challenges they encounter, and the possible ways to improve the current practice. The study involved conducting in-depth interviews with expert panels, including clinicians, dietitians, nurses, and academic professionals who are involved in clinical or teaching practices related to EN. The recording of the interview was transcribed verbatim after each session. The coding process was done using the computer-assisted qualitative data analysis software Atlas-Ti. The thematic analysis procedure by Braun and Clarke is used to analyze the transcription. At the end of the study, eleven interviews were conducted, transcribed, and analyzed. Six themes addressing the challenges in EN were identified. The themes are standardization of EN practice, enteral feeding provision, knowledge of nurses, attitude of HCPs, skills of nurses, and resources in the healthcare facility. In addition to that, four themes addressing the current needs of EN practice were also documented. The themes identified are EN guidelines and protocols, improving Knowledge, Attitude, and Practice (KAP) on EN, continuous education on EN, and improving healthcare facilities. The insights shared by the participants can be thoroughly examined to develop strategies for enhancing existing EN processes.